2014
DOI: 10.1007/s10571-014-0066-5
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of the Connexin 43 Elevation May be Involved in the Neuroprotective Activity of Leptin Against Brain Ischemic Injury

Abstract: Leptin is a multifunctional hormone produced by the ob gene and is secreted by adipocytes that regulate food intake and energy metabolism. Numerous studies demonstrated that leptin is a novel neuroprotective effector, however, the mechanisms are largely unknown. Herein, we demonstrate the protective activities of leptin after ischemic stroke and provide the first evidence for the involvement of the connexin 43 (Cx43) in leptin-mediated neuroprotection. We found that leptin treatment reduces the infarct volume,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 25 publications
0
24
0
Order By: Relevance
“…Cx43 Is Increased After HI Injury While brain injury has been shown to increase Cx43 expression in brain and retina (Danesh-Meyer et al, 2012;Deng et al, 2014;Haupt et al, 2007), there is no prior study on Cx43 expression after cerebral HI injury in neonatal rats. In this study, we examined the dynamic expression of Cx43 after HI injury.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Cx43 Is Increased After HI Injury While brain injury has been shown to increase Cx43 expression in brain and retina (Danesh-Meyer et al, 2012;Deng et al, 2014;Haupt et al, 2007), there is no prior study on Cx43 expression after cerebral HI injury in neonatal rats. In this study, we examined the dynamic expression of Cx43 after HI injury.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have shown that ischemic injury increases Cx43 expression in brain and retina (Danesh‐Meyer et al ; Deng et al, ; Haupt et al, ). In our study, we found that OGD increased expression of Cx43 not only in the membrane but also in cytoplasm.…”
Section: Discussionmentioning
confidence: 98%
“…Although this study does not allow us to directly test this hypothesis, we note that putative protective effects of leptin have been reported, as increased leptin serum levels facilitate learning and memory performance in preclinical studies, 39 and have a neuroprotective role in ischemic brain injury. 40 Translational studies, however, are needed to fully address the possible cross-talk between ghrelin and leptin in alcohol craving and drinking.…”
Section: Discussionmentioning
confidence: 99%
“…Both Cx40 and have been shown to be associated with brain pathophysiology. For example, Deng et al reported that inhibition of Cx43 by leptin contributes leptin’s neuroprotective activity against brain ischemic injury [ 6 ]. Merier and colleagues detected the differences in expression of Cx43 in response to brain injury, and they also found overexpression or deletion of Cx43 was associated with the pathophysiological outcome [ 7 ].…”
Section: Introductionmentioning
confidence: 99%